Aging as an Evolvability-Increasing Program Which can be Switched Off by Organism to Mobilize Additional Resources for Survival - V. Skulachev, Maxim; F. Severin, Fedor; P. Skulachev, Vladimir (Current Aging Science, 2015)
During the last decade, several pieces of convincing evidence were published indicating that aging of living organisms is programmed, being a particular case of programmed death of organism (phenoptosis). Among them, the following observations can be mentioned. (1) Species were described that show negligible aging. In mammals, the naked mole rat is the most impressive example. This is a rodent of mouse size living at least 10-fold longer than a mouse and having fecundity higher than a mouse and no agerelated diseases. (2) In some species with high aging rate, genes responsible for active organization of aging by poisoning of the organism with endogenous metabolites have been identified. (3) In women, standard deviations divided by the mean are the same for age of menarche (an event controlled by the ontogenetic program) and for age of menopause (an aging-related event). (4) Inhibitors of programmed cell death (apoptosis and necrosis) retard and in certain cases even reverse the development of age-dependent pathologies. (5) In aging species, the rate of aging is regulated by the individual which responds by changes in this rate to changes in the environmental conditions. In this review, we consider point (5) in detail. Data are summarized suggesting that inhibition of aging rate by moderate food restriction can be explained assuming that such restriction is perceived by the organism as a signal of future starvation. In response to this dramatic signal, the organism switches off such an optional program as aging, mobilizing in such a way additional reserves for survival. A similar explanation is postulated for geroprotective effects of heavy muscle work, a lowering or a rise in the external temperature, small amounts of metabolic poisons (hormesis), low doses of radiation, and other deleterious events. On the contrary, sometimes certain positive signals can prolong life by inhibiting the aging program in individuals who are useful for the community (e.g., geroprotective psychological factors). Similarly, dangerous individuals can be eliminated by programmed death due to operation of progeric psychological factors. The interplay of all these signals results in the final decision of the organism concerning its aging – to accelerate or to decelerate this process. Thus, paradoxically, such an originally counterproductive program as aging appears to be useful for the individual since this program can be switched off by the individual for a certain period of time, an action that thereby increases its resources in crucial periods of life.
Keywords: non-aging organisms